الصناعة 4.0 وتقنية البلوكشين والبيانات الضخمة في مجال سلاسل التوريد: مراجعة تحليلية - ابولقاسم محمد على انفيص; حسين خليفة موسى; ايمان بلقاسم رحال (Surman Journal of Science and Technology, 2024)
The use of technology has become an essential requirement in supply chain management operations. Research in digital supply chain management (SCM) has recently emerged as a trending area of study. This study aims to explore and summarize the research conducted thus far in this field and highlights future research prospects for integrating digitalization with supply chain management. To conduct this study, we performed a systematic literature review using multiple software tools to classify the current literature on digital SCM. Our findings indicate that Industry 4.0, Big Data, Blockchain, and supply chain resilience represent the four main categories in digital SCM research. This study explains the rationale behind the research focus on these four categories. This review helps researchers build a comprehensive understanding of the current research landscape in digital SCM and contributes to guiding future research to further explore the combination of SCM with Industry 4.0, Big Data, Blockchain, and supply chain resilience.